Seismic behavior of hybrid systems made of PR composite frames coupled with dissipative bracings. - Amadio, C. (Earthquake engineering & structural dynamics.)
The paper investigates the dynamic behaviour of hybrid systems made of partially restrained (PR) steel concrete composite frames coupled with viscoelastic dissipative bracings. A numerical model that accounts for both the resisting mechanisms of the joint and the viscoelastic contribution of the dissipative bracing is introduced and briefly discussed. The model is first validated against experimental outcomes obtained on a one storey two bay composite frame with partial strength semi-rigid joints subjected to free vibrations. A number of time history analyses under different earthquake ground motions and peak ground accelerations are then carried out on the same type of frame. The purpose is to investigate the influence of the type of beam to column connection and property of the viscoelastic bracing on the performance of the hybrid system. The inherent stiffness of the bare PR frame and the plastic hysteresis of the beam to column joints, which always lead to only limited damage in the joint, are found to provide a significant contribution to the overall structural performance even under destructive earthquakes. This remakr leads to the conclusion that the viscoelastic bracing can be effectively used within the hybrid system.